National and subnational coverage and inequalities in reproductive, maternal, newborn, child and sanitary interventions in Ecuador: a study of national surveys 1994-2012 - Quituizaca, Paulina Belén Ríos (2021)
Introduction: The measurement of social inequalities in health and inequalities in the coverage of interventions allows identifying vulnerable subpopulations, quantifying the gaps, and improving decision-making. Ecuador has little evidence of RMNCH health interventions (reproductive, maternal, neonatal, and infantile). Like several countries in Latin America (LA), they have gone through constant economic and political crises that coincide with periods of social inequalities in health, with little written evidence about it. The objective of this thesis was to analyze the inequalities in the coverage of the RMNCH and WAS (drinking water and sanitation) interventions at the individual, geographical and temporal level. Methods: A cross-sectional analytical descriptive study was designed, which used national survey databases from 1994, 1999, 2004, and 2012. The coverage of the interventions was calculated based on standardized criteria. The stratifies used were: quintiles as a measure of socio-economic inequality, urban-rural residence, and province. The analysis of the stratifies broadens the understanding of the problem and the alternative solutions, and the temporal analysis allows us to understand how political and economic circumstances are linked to the results of health interventions. For the periods 2004 to 2012, ethnic self-identification was analyzed, considering the mother\'s education and wealth quintiles. Absolute, relative, simple, and complex measures of inequalities were used, including Theil index, Moran index, and multivariate adjustment models for the analysis of ethnicity. Results: The most significant RMNCH inequality gaps in Ecuador coincide with periods of neoliberal policies and lower social spending (period 1994-2004, as opposed to 2012). The WAS interventions were the most unequal; the rich had 2.4 times more coverage in improved sanitation facilities than the poorest. Although the difference in coverage between provinces has been enhanced for the 2012 period (Diff 1999 = 31.6, Diff 2004 = 33.5, Diff 2012 = 13.6), evident and historical inequality gaps are identified. The population that identifies itself as indigenous maintains the lowest levels of schooling (74.4% up to primary level), and the majority belong to the lowest quintiles of poverty (50.7% in the poorest quintile 1). After adjusting for education and wealth, there is still a 35% lower prevalence of births attended by qualified personnel, 28% less coverage of prenatal check-ups, and 24% lower prevalence of modern contraceptives. Conclusions: It is urgent to strengthen social spending policies and prioritize the vulnerable population, especially those with a historical disadvantage, such as indigenous and Afro groups. It is necessary to identify disadvantaged groups and analyze the political, social, and cultural contexts of the subpopulations, to influence the impact indicators on maternal and child health; since national averages hide local realities. These strategies must be locally adapted, generating different measurement indicators that reflect this adaptation and continuously monitored.